THE CORRELATION STUDY ABOUT PREJUDICE AND SOCIAL CONFLICTS ON ISLAM NUSANTARA IN PADANG - Reza Fahmi; Prima Aswirna; Syafruddin Nurdin (Islam Futura, 2020)
The research objectives: (1) Describe the prejudices of community leaders about Islam Nusantara. (2) Describe the picture of people's prejudices about Islam Nusantara. (3) Connecting between the prejudices of religious leaders and the community and its relation to the social conflict of the people of the city of Padang. The study uses qualitative approaches and quantitative mixing methods (mixed methods). The population in this study were 32 religious leaders and 168 community members. Data collection techniques using; observation, interview and psychological scale. A simple random sampling technique. Data analysis techniques using Pearson correlation. The results of this study found that generally the negative prejudices of religious leaders about Islam Nusantara were high. While social conflict in the midst of society is classified as low. Whereas them correlation aspect shows that there is no correlation between the views of religious leaders and community members about Islam Nusantara not correlating with social conflict in the midst of society.